Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2008
DOI: 10.1074/jbc.m803447200
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Functional Characterization of Transmembrane Segment IX of the NHE1 Isoform of the Na+/H+ Exchanger

Abstract: The Na؉ /H ؉ exchanger isoform 1 (NHE1) is an integral membrane protein that regulates intracellular pH by removing one intracellular H ؉ in exchange for one extracellular Na ؉ . It has a large N-terminal membrane domain of 12 transmembrane segments and an intracellular C-terminal regulatory domain. We characterized the cysteine accessibility of amino acids of the putative transmembrane segment IX (residues 339 -363). Each residue was mutated to cysteine in a functional cysteineless NHE1 protein. Of 25 amino a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
3

Relationship

5
3

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 61 publications
1
36
0
Order By: Relevance
“…Their structure is more similar to that of part of TM 7 and 8 with a link in between. In addition, the same study 35 showed that Ser 351 is a pore lining residue which is in agreement with model 2's predictions.…”
Section: Model 2 31 (supporting
confidence: 78%
See 2 more Smart Citations
“…Their structure is more similar to that of part of TM 7 and 8 with a link in between. In addition, the same study 35 showed that Ser 351 is a pore lining residue which is in agreement with model 2's predictions.…”
Section: Model 2 31 (supporting
confidence: 78%
“…Additionally, there have been nuclear magnetic resonance (NMR) studies on individual putative TM helices of NHE1 taken from the Wakabayashi model. The solution NMR structures have been elucidated for the putative TM segments IV, VII and IX [33][34][35] while that of TM XI has also been determined (unpublished observation). This detailed structural information allows more informed functional assays as well as the prediction of the molecular mechanism of NHE1 function.…”
Section: Nhe Structure First Insightsmentioning
confidence: 99%
See 1 more Smart Citation
“…This was done to aid solubilization of the peptide as described earlier (13,15). The primers SodMBPf (5Ј-CATGGGATCCAAAAAAAAATTGT-TTCCACAAATTAACTTTTTAGG-3Ј) and SodMBPr (5Ј-CCGGGAATTCTCATTTCTTTTTTCCTACAATCAATG-CTGATAG-3Ј) were used to amplify the DNA of sod2 and add the terminal lysines.…”
Section: Methodsmentioning
confidence: 99%
“…TM IX contains two structurally conserved regions containing ␣-helix structure at residues 340 -344 and 353-359, with a 90°kink at Ser 351 between the two regions that could potentially provide flexibility. Cysteine scanning mutagenesis showed that both residues Ser 351 and Glu 346 , between the helical regions, are pore-lining (18). TM XI contains two helical regions, residues 447-454 and 460 -471, and Leu 465 was identified as pore-accessible through cysteine scanning mutagenesis and reaction with MTSET (19).…”
mentioning
confidence: 99%